PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA MATA PELAJARAN IPS DI KELAS VII.7 SMP NEGERI 22 PEKANBARU - RUKIAH RUKIAH (Universitas Riau, 2017)
The student’s activity and the students achievments in Grade VII.7 of SMPN22 Pekanbaru are far from satisfaction. This Research was aimed to increase the activitiesand the students achieviement by using Cooperative Learning of STAD Type in learning IPS.The data of of the activities was analized by finding out the percentage of the students involvedin every meeting. The increase of the achieviement was from the number of students whoachieved throroughness score and the average score gained at the end of the cycle. However,this is because the cooperative learning model of STAD type is more focusing on the studentsas the subject of learning and giving the students more chance to construct there knowledgefinally, in general it can be concluded that the use of cooperative learning model of STAD typeis able significantly to increase the students activities and the learning achieviement on IPS bystudents of grade VII.7 of SMPN 22 Pekanbaru.